Wave propagation in magnetic media - Fermín, José; Rivas Suárez, Ronald (Ciencia, 1970)
The purpose of this work is to investigate on the phenomenon of front propagation intomagnetic media. Here, we study the case when the magnetization, M, is driven by a dc applied magnetic field, H0, from the demagnetized to the magnetized state. A theoretical model is presented for solving the Landau- Lifshitz- Gilbert equation (LLGE) in the framework of an effective field that includes first order cubic, H1, inplane uniaxial, HU, and shape anisotropy fields, HD. It is show that the dynamics of the magnetization is govern by a diffusion- reaction equation, and in the important case of uniformly translating profiles, this equation gives a family of solutions that describe harmonic oscillating (HO), damped oscillating (DO), exponential fronts (EF), amplified oscillating (AO), and dual front profiles (DF). Also of interest is the existence of a critical front speed, v*, that separates the damped oscillations from the exponential fronts. In the case of purely uniaxial systems, this velocity is connected with the existence of a nonlinear marginal stability point for front propagation, and shows a strong dependence on the relative value of the anisotropy constants of the medium. When the crystalline anisotropy overcomes the uniaxial field the marginal stability point is not well defined since v* is purely imaginary and only exponential fronts are linearly stable.